Age-related Differences in Recall of Information and Handling of Chemotherapy-related Side Effects in Cancer Patients: The ReCap Study. (9th February 2022) - Lund, Cecilia Margareta; Mikkelsen, M K; Theile, S; Michelsen, H M; Schultz, M; Sengeløv, L; Nielsen, D L
Abstract: Background: To prevent severe toxicity and hospital admissions, adequate management and recall of information about side effects are crucial and health literacy plays an important role. If age-related factors impact recall of given information and handling of side effects, revised ways to give information are required. Patients and Methods: We undertook a questionnaire-based survey among 188 newly diagnosed patients with pancreatic cancer or colorectal cancer and chemo-naive patients with prostate cancer treated with adjuvant or first-line palliative chemotherapy comprising satisfaction with given information, recall of potential side effects, and handling of hypothetical side effect scenarios. We evaluated the association between baseline characteristics, ie, age, frailty (G8 score), comorbidity (Charlson Comorbidity Index), cognitive function (Mini-Cog), satisfaction, recall of information, and handling of side effects. Results: Reduced ability to recall information about several side effects (eg, chest pain) was associated with older age (odds ratio adjusted for cancer [aOR] 0.94 [95% CI, 0.88-0.98]) and poor cognitive screening (aOR 0.56 [95% CI, 0.33-0.91]). Insufficient or dangerous handling of side effects was associated with older age (aOR 0.96 (95% CI, 0.92-0.99)) and cognitive impairment (aOR 0.70 [95% CI, 0.50-0.95]). Conclusion: Older age and poor cognitive screening may impact patients' ability to understand and adequately handle chemotherapy-related side effects. Cognitive screening and focus on individual ways to give information including assessment of recall and handling are needed. Abstract : Health literacy and a patient's ability to be aware of side effects and morbidity are crucial in the trajectory of cancer treatment. This article reports on the effect of age-related variables on the recall of information to adequately handle treatment-related side effect in patients with newly diagnosed cancer.